Hemagglutinin protein of Peste des Petits Ruminants virus (PPRV) activates the innate immune response via Toll-like receptor 2 signaling - Rojas, José M. (Virulence, 2021)
The toll-like receptor (TLR) family comprises both cell-surface and intracellular receptors that recognize different types of pathogen-associated molecular patterns (PAMPs) leading to the production of pro-inflammatory cytokines and subsequent development of adaptive immunity. TLR2 is a cell-surface receptor initially thought to act as a bacterial sentinel but also shown to recognize a number of viral glycoproteins. In this study, we sought to characterize the role of TLR2 in the activation of the immune response by peste des petits ruminants virus (PPRV), a morbillivirus of the Paramixoviridae family that causes an acute, highly contagious disease in goats and sheep. Using human embryonic kidney (HEK) 293 cells stably expressing human (h)TLR2 but lacking any other TLR, we found that PPRV induces IL-8 production in a dose-dependent manner. That activation is only observed in cells expressing hTLR2 and is greatly reduced when the receptor is blocked by pretreatment with specific antibody. We identified hemagglutinin (H) as the viral protein responsible of TLR2 activation by performing the same assays with purified recombinant mammalian-expressed H protein. Exogenous addition of recombinant H protein to cell culture induces high levels of interleukin (IL)-8 only in TLR2-expressing cells. Moreover, H engagement on TLR2 in the monocytic cell line THP-1 activates extracellular-signal-regulated kinase (ERK) signaling. Stimulation of primary ovine dendritic cells with either inactivated PPRV or purified recombinant H protein results in transcription of pro-inflammatory cytokines and the secretion of the Th1-polarizing cytokine IL-12. The role of these host immune mechanisms in the control of PPR is discussed.